The Constancy of Perceived Motion Under Different Spectral Conditions - Jeffrey Nightingale; James M. Brown; Billy R. Hammond (Vision)
(1) Background: Perceptual constancies are found in numerous categories of visual perception; color, lightness, and size constancy are notable examples where the perception of a visual scene remains constant, even with changing optical conditions. Constancies such as these are essential for survival, as they reduce the unpredictability of the world. In this study, we tested the resiliency of motion perception under widely differing spectral conditions. (2) Methods: Sixty healthy subjects (age range 18 to 26) were tested. Motion perception performance and thresholds were assessed using a novel, ecologically valid, psychophysical task implementing modern instruments. A broadband xenon bulb was used as a light source to emulate the spectral characteristics of natural daylight; 3 filter conditions were included to emulate different conditions of environmental light (short-wave, 400 nm–500 nm; medium-wave, 500 nm–600 nm; and long-wave, 600 nm–700 nm). (3) Results: In general, our findings showed that varying the spectral content of the broadband source did not change motion perception performance or thresholds for subjects. (4) Conclusions: These findings indicate that motion perception is highly resistant to changes in optical conditions, such as dramatically different spectral illuminants. This evidence is consistent with motion being considered among the perceptual constancies.